STRATEGIES TO INCREASE MUSLIM CONSUMER LOYALTY IN THE TIME OF THE COVID-19 PANDEMIC - Kusumawati, Dyah; Andayani, Sri Umiatun; Suparto, Diryo (UIN Salatiga, 2021)
This study was conducted to determine the extent of the influence of promotional strategies, product quality, and customer satisfaction on customer loyalty to Indosat Ooredoo card customers. The type of research used is explanatory research. The population is all Indosat Ooredoo card customers in Demak Regency. The technique of determining the sample is by purposive sampling. In this study, the number of samples used was 131 respondents. Data analysis was performed using multiple linear regression analysis techniques. Data collection techniques through online questionnaires using a Likert scale. Sources of data are primary data and secondary data. The results of this study based on partial testing in this study are each variable namely promotion strategy, product quality, and customer satisfaction has proven to have a positive and significant effect on customer loyalty. Based on the results of simultaneous testing, it is in a strong category because promotion strategies, product quality, and customer satisfaction are proven to have a positive and significant effect on customer loyalty.